Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/2110-5820-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of lactate monitoring in critically ill patients

Abstract: Increased blood lactate levels (hyperlactataemia) are common in critically ill patients. Although frequently used to diagnose inadequate tissue oxygenation, other processes not related to tissue oxygenation may increase lactate levels. Especially in critically ill patients, increased glycolysis may be an important cause of hyperlactataemia. Nevertheless, the presence of increased lactate levels has important implications for the morbidity and mortality of the hyperlactataemic patients. Although the term lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
272
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(317 citation statements)
references
References 66 publications
3
272
1
6
Order By: Relevance
“…In critical illness, there is usually concurrent hypoalbuminaemia which covers the metabolic acidosis [16]. Also the unmeasured ions leads to change in anion gap, anions increase , whereas cations decrease the anion gap.…”
Section: Discussionmentioning
confidence: 99%
“…In critical illness, there is usually concurrent hypoalbuminaemia which covers the metabolic acidosis [16]. Also the unmeasured ions leads to change in anion gap, anions increase , whereas cations decrease the anion gap.…”
Section: Discussionmentioning
confidence: 99%
“…When perfusion is maintained the lactate level may decrease. (28) According to the 1997 WHO guideline, plasma leakage is determined by the presence of hemoconcentration as reflected by increased hematocrit level of ≥20% and/or thrombocytopenia of <100,000/mm 3 . A limitation to these criteria is that baseline hematocrit values are commonly not available, and may be misleading in the presence of anemia or hemorrhage and during the early phase of resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the rate of glycolysis can increase faster by several orders of magnitude than oxidative phosphorylation, glycolysis can briefly provide far more ATP when most required under stress conditions. Excess pyruvate will rapidly accumulate and is diverted to lactate in order for glycolysis to proceed [4]. It could be concluded that the observed hyperlactatemia is due to decreased anaerobic threshold and premature entering the anaerobic system with accelerated glycolysis that overwhelms lactate utilization and clearance.…”
Section: Organ Function and Metabolic Stressmentioning
confidence: 99%
“…Although hyperlactatemia is frequently used to diagnose inadequate tissue oxygenation, other processes not related to tissue oxygenation may increase lactate levels. The current hyperlactatemia mostly refers to lactate potential to serve as a critical buffer allowing glycolysis to accelerate when large additional amounts of energy are rapidly required under circumstances of ironinduced cellular stress [4]. Iron-induced hyperlactatemia could thus be due to impaired lactate clearance rather than hypoxic tissue production of lactate [7].…”
Section: Organ Function and Metabolic Stressmentioning
confidence: 99%
See 1 more Smart Citation